2017
DOI: 10.1002/chem.201701572
|View full text |Cite
|
Sign up to set email alerts
|

Differential Attenuation of NMR Signals by Complementary Ion‐Exchange Resin Beads for De Novo Analysis of Complex Metabolomics Mixtures

Abstract: A primary goal of metabolomics is the characterization of a potentially very large number of metabolites that are part of complex mixtures. Application to biofluids and tissue samples offers insights into biochemical metabolic pathways and their role in health and disease. 1D H and 2D C- H HSQC NMR spectra are most commonly used for this purpose. They yield quantitative information about each proton of the mixture, but do not tell which protons belong to the same molecule. Interpretation requires the use of NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…DOSY-type experiments applied to complex mixtures, on the other hand, may not have sufficient resolution along the diffusion dimension to discriminate between different molecules. An approach to address this situation has been proposed recently, which is based on complementary ion exchange resin beads (e.g., 30–300 μm) to differentially attenuate 2D NMR cross-peaks that belong to different metabolites [ 46 ]. Based on their characteristic attenuation patterns, cross-peaks could be clustered and assigned to individual molecules, including metabolites with multiple spin systems, as demonstrated for a metabolite model mixture and E. coli cell lysate.…”
Section: Nanoparticle-metabolite Interaction Assist Metabolite Detmentioning
confidence: 99%
“…DOSY-type experiments applied to complex mixtures, on the other hand, may not have sufficient resolution along the diffusion dimension to discriminate between different molecules. An approach to address this situation has been proposed recently, which is based on complementary ion exchange resin beads (e.g., 30–300 μm) to differentially attenuate 2D NMR cross-peaks that belong to different metabolites [ 46 ]. Based on their characteristic attenuation patterns, cross-peaks could be clustered and assigned to individual molecules, including metabolites with multiple spin systems, as demonstrated for a metabolite model mixture and E. coli cell lysate.…”
Section: Nanoparticle-metabolite Interaction Assist Metabolite Detmentioning
confidence: 99%
“…Um die Identifizierung neuer Metabolite in biologischen Matrices zu verbessern, wurde eine Trennvorschrift vorgeschlagen, bei der die Lösung einer NMR‐Metabolomik‐Mischung durch eine Serie von Filtern gegeben wird, die entweder mit anionischen oder kationischen Ionenaustauscherharz‐Kügelchen (IERB, ion exchange resin beads) beladen sind. Auf diesem Wege werden die Metabolite nach ihren spezifischen physikochemischen Eigenschaften aufgetrennt . Daher können die 1 H‐ 13 C‐HSQC‐2D‐Spektren des Durchflusses und des Eluats für eine bessere Zuordnung der Metabolite verwendet werden.…”
Section: Technische Verbesserungenunclassified
“…Recent progress in machine learning has enabled the development of de novo molecule generators, [23][24][25][26][27] which are expected to design molecules with desired properties. 28 For instance, we developed a molecule generator, ChemTS, 27 which combines Monte Carlo tree search (MCTS) with a recurrent neural network (RNN), and successfully showed that ChemTS coupled with quantum chemical calculations can produce realistic molecules that have desired properties. 29 So far, most de novo molecule generators have only been tested or applied on quantifiable chemical properties such as HOMO-LUMO gaps.…”
Section: Introductionmentioning
confidence: 99%